PENGARUH PROPORSI TEPUNG UBI KUNING, MOCAF, TEPUNG KACANG KEDELAI TERHADAP GIZI MAKRO, SERAT, DAN NILAI SENSORI SNACK BAR - Ayu - Qoriah (Universitas Muhammadiyah Gresik, 2021)
Yellow yam flour, mocaf and soybean flour are sources of complex carbohydrates with high fiber. The purpose of this study was to determine the effect of the proportions of yellow yam flour, mocaf, and soybean flour on the levels of macronutrients, crude fiber, and sensory snack bar products. The research method used an experimental design with a completely randomized design consisting of 1 control formula (F0) and 3 treatment formulas (F1, F2, and F3). The research data were analyzed using the ANOVA test and Duncan's further test. The organoleptic test used consumer panelists with 30 panelists whose results were analyzed using the Kruskal Wallis test. The results of the chemical test of macronutrients and crude fiber content were different from the P-value sig. < 0.05. The protein content of code F0, F1, F2 and F3 is 5.40 g; 7.98 g; 8.35 g; 8.60 g. The fat content is 14.91 g; 15.36 g; 15.97 g; 16.12 g, the carbohydrate content is 54.05 g; 52.89 g; 52.80 g; 52.50 g, the crude fiber content is 1.24 g; 3.77 g; 4.19 g; 4.61 g. Even though, the results of the hedonic test for each formulation (F0, F1, F2 and F3) for the color and taste parameters there are differences with the asym sig value of the parameter being 0.00. Though, the aroma and texture parameters there is no difference with the asymp value. Sig 0.12 and 0.09. The most preferred mean rank on the snack bar is the formula F0 (74.61), the preferred treatment formula is F3 (58.65).